(untitled) (International Journal of Built Environment and Sustainability, 2025)
Heritage cities encompass a wide array of tangible and intangible cultural resources, including historical structures, architectural styles, customs, and cultural environments. The field of place attachment has been extensively studied, and the issue persists, particularly about the erosion of local values caused by the rapid expansion in historic cities. Furthermore, recent studies have placed growing emphasis on the problem of wellbeing, particularly in relation to the built environment. This study aims to explore the role of place attachment towards local community wellbeing. In this study, a quantitative method was carried out on 173 respondents around the Johor Bahru heritage city, which includes the dimension of place attachment as well as the subjective wellbeing. Spatial and behavioural analysis revealed that respondents living within 5 km of the heritage area reported the highest visitation frequency, with 70.6% visiting daily and more than 60% visiting 2–4 times monthly. The result indicates that the longer and more frequent respondents spend time in the heritage city, the stronger the attachment that can be felt. However, the physical proximity alone does not significantly impact wellbeing. Besides that, the result shows that the Johor Bahru heritage city still has a place attachment value, but at a low and moderate level. Place identity showed the highest correlation with positive affect (r = .589, p < .001), while place dependence and social bonding also correlated with higher life satisfaction (r = .320, p < .001 and r = .315, p < .001, respectively). However, negative affect was weakly associated with place attachment variables, with no significant correlations found for social relations (r = 0.006, p = 0.936) and place dependence (r = 0.101, p = 0.187) with negative emotions. Personal inclination to narrate stories about one’s city is identified as a powerful indicator of strong correlation between variables. This study opened that method proposed can produce a reliable data that can be statistically analysed to identify the patterns and connection between variables.